The Role of Unmanned Vehicles in Enhancing Marine Logistics Security - Sabaruddin Rahman (Collaborate, 2024)
Marine logistics security is a crucial aspect of maintaining a smooth global maritime supply chain. This article explores the role of unmanned vehicles (UVs) such as unmanned aerial vehicles (UAVs) and unmanned underwater vehicles (UUVs) in enhancing ocean logistics security. UVs offer a cost-effective and flexible solution to monitor large ocean areas with advanced reconnaissance, monitoring, and tracking capabilities. This article analyses current UV technologies, advantages and limitations, and challenges in integrating UVs into marine logistics security operations. It also discusses the legal, ethical, and policy implications of using UV in the maritime context. Given the huge potential of UV in improving security and efficiency, this article highlights the importance of collaboration between industry and government stakeholders to optimize the utilization of this technology.